PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Dina Maria Goretti Simbolon; Cristin Pebriola; Rhema Maya Yemima Waruwu; Jholant Bringg Luck Amelia Br Sinaga; Munawarah (Journal Accounting International Mount Hope, 2024)
Using a sample of 87 annual reports of food and beverage manufacturing companies in Indonesia from 2019-2021, the study found that liquidity, solvency and profitability had an impact on the stock price while for the size of the company there was no influence on the share price. The results indicated that the company's size could not yet be used as a factor of consideration that could influence the price of the stock. However, the likvidity, Solvency, and Profitability could be used in terms of influencing stock prices.